2022
DOI: 10.1111/jocd.14442
|View full text |Cite
|
Sign up to set email alerts
|

Mobile shopping beauty live commerce changes in COVID‐19 pandemic focused on fun contents of MZ generation in Republic of Korea

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is the new virus responsible for the coronavirus disease 2019 (COVID‐19) pandemic. According to these circumstances, a study was conducted to prepare a long‐term non‐face‐to‐face outpatient treatment service during the COVID‐19 pandemic. Given the current situation of the times, it is expected that there will be no return to the non‐face‐to‐face prior. Objectives Therefore, this study descriptively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…On the other hand, the streamers' persuasiveness (Gao et al, 2021), humor appeal and sex appeal (Hou et al, 2020) also positively impact consumers' watching intention and purchase intention. In addition, studies from different Asian countries (e.g., South Korea Lee and Kwon, 2022, Thailand Chandrruangphen et al, 2022, and Malaysia Ong et al, 2021 have also confirmed similar conclusions.…”
Section: Live Commercementioning
confidence: 72%
“…On the other hand, the streamers' persuasiveness (Gao et al, 2021), humor appeal and sex appeal (Hou et al, 2020) also positively impact consumers' watching intention and purchase intention. In addition, studies from different Asian countries (e.g., South Korea Lee and Kwon, 2022, Thailand Chandrruangphen et al, 2022, and Malaysia Ong et al, 2021 have also confirmed similar conclusions.…”
Section: Live Commercementioning
confidence: 72%
“…It said there is a need for continuous research. As such, the surge in online purchases due to COVID‐19 has brought about a major change in the purchasing behavior of beauty product consumers 11,13,14 1 summarizes the COVID‐19 untact era and changes in purchasing patterns in the beauty market.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that a new era will come, centering on those who have emerged as new consumers in a market where individual tastes and individuality are emphasized. It will be paid attention to their consumption trends 13 . In addition, the proliferating fandom they are leading will enable a relationship with brand value and true meaning through inbound marketing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cosmetic industry that has changed in the untact era will spread into a new beauty live commerce market. 34 As a result, it was said that live commerce and influencer attributes were regarded as evaluation criteria and that they were recognized as repurchase intentions of beauty and fashion products. Due to lifestyle changes in the use of digital platforms, the use of packaging materials is increasing, and, accordingly, environmental issues are becoming more important.…”
Section: Discussionmentioning
confidence: 99%